Development of Innovative Particleboard Panels - Francesco Balducci (University of Zagreb, Faculty of Forestry and Wood Technology, 2008)
One aim of a joint European project called DIPP (Development of Innovative Particleboard (chipboard) Panels for a better mechanical performance and a lower environmental impact) is the development oflightweight particleboards made from annual/perennial farm plants such as hemp, sunflower, topinambur, maize and miscanthus. These lightweight particleboards are intended as a possible substitution for traditional wood-based particleboards used in the furniture industry. Therefore the requirements of the EN 312 concerning themoisture-related and mechanical properties of boards for interior use have to be met. The results of research have shown that the internal bond strength of one-layer lightweight particleboards made in the experiment meets the requirements of EN 312 (type P2) and the internal bond strength of three-layer boards with topinambur in the core layer does not meet these requirement. The lightweight boards failed to meet the requirements of modulus of elasticity and bending strength.